Analytical analysis of modulation instability in fiber optics - M. Saeed Aslam; M. Yousaf Hamza; Nadeem Sarwar (AIP Advances, 2012)
In this paper, an improved analysis for modulation instability, which results from interaction between optical wave and noise, is presented. It is shown that Nonlinear Schrodinger equation (NLSE), which governs this process, leads to the coupled wave equations that result to Riccati's differential equations. A completely analytical solution of Riccati's equation is obtained for small fiber length that results in efficient computation of the modulation instability effect.